Effect of salt stress on osmoregulation and energy consumption in grass carp Ctenopharyngodon idella (Val.,1844) - Jaafar, Raghad S.; Ahmed, Sumaya M. (Iraqi Journal of Aquaculture, 2022)
This study aims to explain the effect of salt stress on Grass carp Ctenopharyngodon idella. It includes two parts, the first to determine the LC50 during abrupt increase in salinity to 5,10 and 15g/L.While the other part concerned with the physiological effects of the gradual increase in salinity to 5 and 10 g/L on osmoregulation, by measuring ions concentration ( Na+, K+ ) in the blood plasma and muscles, water contents in the muscles , numbers and percentage of chloride cells in the gills epithelia, beside studying the expenditure of osmoregulation by measuring the rate of oxygen consumption, the levels of glucose and total protein in blood plasma. The results showed that the Grass carp has a narrow salt tolerance with LC50 7.5g/L. Osmoregulation study showed an increase in the concentrations of ions( Na+ and K+) in the blood plasma and muscles with increasing salinity to 5 and 10 g/L and the water levels in the muscle increase with increasing salinity. These changes are parallel with the increasing percentage and numbers of chloride cells in the gills. The oxygen consumption rate was increased with increasing salinity to 5 and 10 g/L .There was a decrease in the total protein and increase in the glucose levels with increasing salinity to 5 and 10g/L which reflect an increase energy consumption for osmoregulation. It was concluded, that the Grass carp does not have resistance to high salt concentration over 10 g/L, and the acclimation occurred in salt concentrations between 5 and 10 g/L with a new state of homeostasis and high consumption of energy for osmoregulation.